The development of sexuality in children in a risk situation - Yano, Karen Murakami; Ribeiro, Moneda Oliveira (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to depict and analyze the development of sexuality in children in a risk situation. Forty-two children, of ages between 6 and 12 years, were interviewed in pairs, using techniques to facilitate communication. The qualitative, descriptive-exploratory method was used, according to Thematic Content Analysis. The lack of guidance and information, the inadequate references and sources of knowledge and the violation of their rights characterize the course of sexuality in these children. Away from fairy tales, they discovered the dichotomy between love and sex, which was associated to violent events.